1997
DOI: 10.1002/art.1780400216
|View full text |Cite
|
Sign up to set email alerts
|

In vitro apoptosis and expression of apoptosis‐related molecules in lymphocytes from patients with systemic lupus erythematosus and other autoimmune diseases

Abstract: Objective. To analyze factors related to apoptosis in systemic lupus erythematosus (SLE) peripheral blood mononuclear cells (PBMC) and to compare the findings in SLE PBMC with those in normal donor PBMC or PBMC from patients with other autoimmune diseases. Methods. PBMC from normal healthy donors or patients with SLE, mixed connective tissue disease (MCTD), rheumatoid arthritis (RA), or various vasculitides were isolated. The percentage of apoptosis after activation through different signaling pathways was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
132
2
2

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 58 publications
13
132
2
2
Order By: Relevance
“…Importantly, we have found nonselective up-regulation of both pro-apoptotic and anti-apoptotic gene products on mRNA or protein levels after PHA stimulation of PBMC for 6 days. The increase in the expression of those gene products seems to be a non-specific consequence of cellular activation, as we could observe up-regulation of fas/Apo-1, bcl-2 or other apoptosis related gene products after cellular activation independent of the quality of the stimulus [55]. Importantly, however, after stimulation of PHA blasts with IL-2 or IL-15 we could not find a selective up-regulation of anti-apoptotic gene products, yet there was significant and rapid inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 70%
“…Importantly, we have found nonselective up-regulation of both pro-apoptotic and anti-apoptotic gene products on mRNA or protein levels after PHA stimulation of PBMC for 6 days. The increase in the expression of those gene products seems to be a non-specific consequence of cellular activation, as we could observe up-regulation of fas/Apo-1, bcl-2 or other apoptosis related gene products after cellular activation independent of the quality of the stimulus [55]. Importantly, however, after stimulation of PHA blasts with IL-2 or IL-15 we could not find a selective up-regulation of anti-apoptotic gene products, yet there was significant and rapid inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 70%
“…Our data show that there does not appear to be any intrinsic functional defect of macrophages from young MRLϩ/ϩ mice to recognize and phagocytose apoptotic thymocytes. It is interesting to note that we found that challenge of macrophages from young MRLϩ/ϩ mice with nucleosomes (as a mimic of in vivo increased cell apoptosis in lupus) [18][19][20][21][22] markedly reduced their ability to phagocytose apoptotic cells. The inhibitory effect elicited by nucleosomes was almost achieved with low concentrations of the autoantigen, and was not a consequence of any cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, however, PBMC from SLE patients were cultured over 6 days before the phagocytic assay. In light of our results, it is conceivable that the observed depressed phagocytosis of apoptotic cells may result, at least in part, from an increased SLE peripheral blood mononuclear cell susceptibility to apoptosis [18,20,38], leading to the release of high levels of nucleosomes [18] and, consequently, to an inhibition in uptake of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human RA peripheral blood cells, the percentage of total apoptosis induced with CD28 mAb/PMA has previously been found similar to that in normal donor peripheral blood mononuclear cells (PBMCs); this phenomenon has been explained by activated T-cell migration to the peripheral joints from peripheral vessels (Emlen et al, 1994;Lorenz et al, 1997). Because PBMCs play an important role in the pathogenesis of various systemic autoimmune diseases, such as systemic lupus erythematosus (Bijl et al, 2001;Funauchi et al, 2001;Papo et al, 1998), Sjögren's syndrome (Zeher et al, 1999), and systemic sclerosis, (Stummvoll et al, 2000), we further investigated this phenomenon in RA.…”
mentioning
confidence: 75%